Monitoring and Evaluation of the Utilization of the Merdeka Mengajar Platform in Education Unit - Mildansyah, Mildansyah; Elfrianto, Elfrianto (Lembaga Riset Mutiara Akbar, 2023)
The development of digital technology has had a significant impact on aspects of education. The Merdeka Mengajar platform provides opportunities for digitalization in terms of increasing competition and curriculum development. This article uses the systematic literature method. The data collection used in this research is to find the results of relevant previous research. The purpose of this article is to see how to monitor and evaluate the use of the Merdeka Mengajar Platform in educational units. The findings obtained show that the Merdeka Mengajar Platform really provides benefits to teachers in teaching and learning activities in the classroom. The conclusion of the Merdeka Mengajar Platform in educational units is that the Merdeka Mengajar Platform can improve teachers' skills and competencies in learning and curriculum development. Apart from that, students can also access various learning materials, videos and interactive activities provided by the Merdeka Mengajar Platform